Analisis Dampak Jumlah Penduduk, Pengangguran, dan IPM terhadap Tingkat Kemiskinan di Provinsi Sumatera Utara 2001-2021 - Maria Elpida Manalu; Karin Sarah Angelina Siahaan; Joko Suharianto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
One of the socioeconomic problems faced by every region is poverty. Poverty is a social issue that takes place in the long term, so that until now it is still difficult to overcome. The purpose of this study was to determine the effect of Population, Open Unemployment Rate (TPT), and Human Development Index on Poverty Level in North Sumatra Province. This study uses secondary data analysis in the form of time series data which is quantitative in nature, namely data in the form of numbers. The secondary data used in this study are poverty data, population data, open unemployment rate data and human development index data from 2001 to 2021. These data were obtained from the North Sumatra in Figures (SUDA) document from 2001 to 2021. The results of this study prove that population has a significant effect on the poverty rate of North Sumatra Province, the open unemployment rate variable has no significant effect on the poverty rate of North Sumatra Province, the human development index variable has no significant effect on the poverty rate of North Sumatra Province. Simultaneously, population, open unemployment rate (TPT), and human development index have a significant effect on the poverty rate in North Sumatra province.